Efficacy of Cyombopogon Citratus Extract Against Enterococcus Faecalis - Tassya Nitulo Permatasari Lahagu; Hyunh Diem An; Cindy Denhara Wijaya; Mellisa Sim (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Endodontic treatment refers to the act of removing infected pulp tissue and forming and reforming the root canals to prevent bacteria from entering the root canals. Microbial infection in the root canal or in the periapical area is a factor that can le ad to failure of root canal treatments. Endodontic treatment failure can be caused the bacteria Enterococcus faecalis. The irrigation agent commonly used is sodium hypochlorite. Sodium hypochlorite in large concentrations can be toxic to tissues. Lemongrass plant (Cymbopogon citratus) is a natural ingredient that can be used as an antibacterial agent. The aims of study to determine the comparison of the antibacterial effectiveness of lemongrass plant extracts (Cyombopogon citratus (DC). Staph) concentrations of 25%, 50%, 75%, 100% with 2.5% sodium hypochlorite in inhibiting the growth of the bacterium Enterococcus faecalis. Lemongrass plant extracts Cyombopogon citratus (DC). Staph) made by maceration method and converted into 25%, 50%, 75%, and 100%. The bacterial test method used the agar diffusion test (Kirby-Bauer test) to see the effectiveness of antibacterialsThe result of the one way ANOVA statistical test resulted in significance value of p=0,001 (p<0,05) so that means there was differences in the ave rage diameter of inhibitory lemongrass plant extracts (Cyombopogon citratus (DC). Staph) concentrations of 25%, 50%, 75%, 100% with 2.5% sodium hypochlorite in inhibiting the growth of the bacterium the results are 13.68 ± 1.34 mm, 16.08 ± 0.87 mm, 16.33 ± 0.35 mm, 17.78 ± 0.93 mm and 7.83 ± 0.44 mm and reinforced by the posthoc Tukey HSD test. The conclusion from the study that there is a difference between the antibacterial effectiveness of lemongrass plant extract (Cyombopogon citratus (DC). Staph) concentrations of 25%, 50%, 75% and 100% with 2.5% sodium hypochlorite in inhibiting the growth of the bacterium Enterococcus faecalis.